Proteomic analysis of exudates in thawed fillets of bighead carp (Hypophthalmichthys nobilis) to understand their role in oxidation of myofibrillar proteins. (January 2022) - Liu, Yueyue; Zhang, Longteng; Gao, Song; Zheng, Yanyan; Tan, Yuqing; Luo, Yongkang; Li, Xingmin; Hong, Hui
Graphical abstract: Created with BioRender.com . Highlights: Frozen storage induces down-regulation of antioxidant enzymes in exudates of fillets. Exudates are capable of oxidizing myofibrillar proteins. Exudates and MDA cause oxidative-crosslinks of MPs in different ways. Abstract: For frozen fillets, the formation of ice crystals destroys the integrity of cell and organelle membranes and causes the release of enzymes that are capable of catalyzing oxidation of myofibrillar proteins (MPs). Exudates from fresh, freeze–thaw (F-T) treated, and frozen stored fillets that were contained those enzymes were collected to explore the protein composition and changes in abundance of the main protein oxidation-related enzymes. Results indicated that enzymes with oxidative capacity were up-regulated and some antioxidant enzymes were down-regulated in exudates collected from 5 months frozen fillets. Changes in abundance of MPs in exudates suggested that degradation of MPs in thawed fillets was a comprehensive result of the F-T treatment, enzymatic degradation, and protein oxidation. The oxidative capacity of exudates was confirmed because incubation with exudates enhanced carbonyls and Schiff bases contents in MPs. Overall, the results of our study suggested that enzymes in exudates were a potential factor in protein oxidation in thawed fillets.